Interdisciplinary research: advancing knowledge and sustainable solutions - Gaydeczka, Beatriz (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
In this issue of the Brazilian Journal of Science, Technology and Innovation (Revista Brasileira de Ciência, Tecnologia e Inovação (RBCTI), we present a selection of studies that reflect the importance of the interdisciplinary approach to understanding and solving the complex challenges we face in different areas of knowledge. This journal aims to promote quality research and foster dialogue between different disciplines, and the articles in this issue highlight the relevance of this approach and its impacts in areas such as aquatic ecology; animal health; civil engineering; socio-environmental impact assessment; cardiovascular health; the association between climate, socio-economic factors and the spatial distribution of arboviruses; and energy.